A miniature X-ray diffraction setup on ID20 at the European Synchrotron Radiation Facility - Christoph J. Sahle; Marta Majkut; Kari O. Ruotsalainen; Florent Gerbon; Noora Suomalainen; Marie-Claire Lagier; Blanka Detlefs; Laurent Claustre; Alessandro Mirone; Alessandro Longo (Journal of Synchrotron Radiation)
We describe an ultra-compact setup for in situ X-ray diffraction on the inelastic X-ray scattering beamline ID20 at the European Synchrotron Radiation Facility. The main motivation for the design and construction of this setup is the increasing demand for on-the-fly sample characterization, as well as ease of navigation through a sample's phase diagram, for example subjected to high-pressure and/or high-temperature conditions. We provide technical details and demonstrate the performance of the setup.